INDIVIDUAL CHARACTERISTICS AND WORK ENVIRONMENT ON TEACHERS OF ENGLISH PERFORMANCE WITH ORGANIZATION - Astri Riance (Universitas PGRI Palembang, 2021)
The goal of this study was to know the influence of individual characteristics and work environment on Teachers of English Performance with organization commitment as a mediator variable. The method of this study was quantitative method, using associative or relationship research methods. The population of this study were 32 teacher of English at SMP Negeri in North Musi Rawas Regency. For the sample was taken by saturated sampling technique, which all the population used as the sample. The data were collected by, observation, questionnaire and documentation. The result of the study show that the Individual Characteristics variable (X1), Work Environment (X2), and Organizational Commitment (Z) to performance (Y), the correlation coefficient value is 0.686. For coefficient interval 0.60 - 0.799. , which means the relationship between the variables of Individual Characteristics, Work Environment, and Organizational Commitment towards teachers shows a strong relationship and a positive correlation value means that the correlation or relationship between Individual Characteristics, Work Environment, and Organizational Commitment to performance is unidirectional.